Nutritional Aspects of Recycling Plants By-Products and Crop Residues (Corn Stalk) in Sheep - Elkholy, M.El.H.; Hassanein, El.I.; Edrees, Nagah; Eleraky, Wafaa; Elgamel, M.F.A.; Ibraheim, Dohaa (Pakistan Journal of Nutrition, 2009)
An experiment was conducted to study the effect of long term feeding of sheep with ureated corn stalk with or without addition of molasses on feed intake, ration digestibility (dry matter, crude protein, ether extract, Ash, crude fiber, neutral detergent fiber and acid detergent fiber) and ruminal parameters which including PH, ruminal TVFA`S and ammonia-nitrogen concentration. The effect of these treatments also on some blood metabolites as (glucose, total protein, total cholesterol, triglycerides, HLD-cholesterol, LDL-cholesterol, VLDL-cholesterol, total protein, albumin, globulin and BUN (Blood urea Nitrogen). The methods of preparation and storage of corn by-products (green corn and corn stalk) when fed as silage which enriched by urea also by yeast with addition of molasses on the same parameters. One year old six healthy Baladi rams, were used in this work (initial average body weight of 30 kg). They were divided into 3 similar groups (2 rams per each group). Crude protein content of treated corn stalk by 4%urea and /or 5% molasses was increased 75.4% and 113.2% respectively due to increase nitrogen content. Feed intake, EE, Ash, crude fiber, ADF and NDF were also significantly decreased. Total digestible nutrients and Digestion Coefficient of DM, OM, EE , NFE and CP did not show any significant difference. Digestion Coefficient of crude fiber fractions (CF, ADF and NDF) were significantly increased. The ruminal Total VFA values were significantly decreased whereas the ruminal Ammonia nitrogen concentration was significantly increased. Moreover, blood glucose, total protein, albumin, globulin and BUN were increased but total lipids, total cholesterol and triglycerides were decreased in treated groups compared with the control.